Influence of number of records and scaling on the statistics of seismic demand for lattice structure. (February 2015) - Li, Y.G.; Fan, F.; Hong, H.P.
Abstract: Seismic design codes prescribe general guidelines to select a small number of ground motion records to be used to calculate the seismic demand for design. In particular, Chinese design codes recommend criteria for selecting three record components and for selecting seven record components to be used for seismic analysis and design. The statistical origin of the criteria as well as the preferred intensity measure for the record scaling are unknown; their adequacy for lattice domes has not been investigated and elaborated. This study evaluates the statistics of seismic responses of the single-layer reticulated dome due to limited number of record components, and investigates the effect of using the PGA and SA based scaling on the statistics of the responses. The time history analysis is carried out using 166 selected record components. Statistics of the maximum of seismic load effects on structural members, support reaction and base shear are obtained based on the analysis results by considering all records, and randomly sampled 3 and 7 records according to code criteria. The results are used to make recommendations on the preferred intensity for scaling the records and the number of record components (three or seven) to be used to analyze and design such domes under seismic load. Highlights: Evaluates the statistics of seismic responses of a lattice dome with sample size effect. Investigated the effect of using different ground motion measures for scaling records. Compared the time history analysis results with those from modal combination rule. Made specific recommendation on the criteria for selecting number of records for analysis.